IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) IN THE INDEPENDENT CURRICULUM IN HISTORY LEARNING AT SMAN 1 RAMBAH, ROKAN HULU REGENCY: IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) PADA KURIKULUM MERDEKA DALAM PEMBELAJARAN SEJARAH DI SMAN 1 RAMBAH, KABUPATEN ROKAN HULU - Siska; Suroyo; Ahmal (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study discusses the implementation of the Pancasila student profile strengthening project (P5) in the independent curriculum in history learning at SMAN 1 Rambah. The purpose of this study was to determine the implementation process of the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum in history learning at SMAN 1 Rambah, to determine the obstacles faced by schools and history teachers in implementing the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum in history learning at SMAN 1 Rambah, to determine the efforts made by schools and teachers in overcoming obstacles in implementing the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum in history learning at SMAN 1 Rambah. This study uses a qualitative research method, with data collection techniques in the form of observation, interviews, and documentation. The subjects in this study were the principal, the curriculum vice principal, and the history teacher. The results of this study indicate that the implementation of the Pancasila student profile strengthening project (P5) in the independent curriculum in history learning at SMAN 1 Rambah has been said to be quite good in its implementation process. The obstacles experienced are the lack of information from the government in implementing P5 in the independent curriculum in schools and the lack of understanding of the school or teachers in implementing the independent curriculum at SMAN 1 Rambah and the lack of understanding of students to learn about P5 in the independent curriculum. The efforts or efforts in implementing P5 are to dig up information on the internet, and take online and offline training, and for teachers to take part in the MGMP program.